Quasi-Clusters in Nuclear Photodisintegration in the Giant Dipole Resonance Region (Global Journal of Science Frontier Research, 2022)
The role of quasi-clusters (systems of a small number of nucleons) in the photodisintegration of light atomic nuclei of the 1p -shell is considered. In these nuclei, there is a strong supermultiplet splitting of levels due to the prominent role of the Majorana forces. It is manifested in the excitation and decay of the Giant Dipole Resonance (GDR), leading to its large-scale configurational splitting. Nucleon quartets, formed inside the nucleus, have a powerful effect on the properties of the GDR of 1p-shell nuclei. The preservation or decay of such quartets during nuclear photoabsorption leads to the formation of various GDR regions. Experimental data confirming this phenomenon are presented.
Keywords: giant dipole resonance; shell nuclei; configurational splitting; supermultiplet structure; Majorana forces; Young schemes; nucleon quartets